Odpowiedź :
a)
½x-2y=8
2x+5y=6
-2y=8-1/2x /*(-1)
2x+5y=6
2y=1/2x-8
2x+5y=6
y=1/4x-4
2x+5(1/4x-4)=6
y=1/4x-4
2x+5/4x-20=6
y=1/4x-4
13/4x=6+20
y=1/4x-4
13/4x=26
y=1/4x-4
x=26*4/13
y=1/4x-4
x=8
y=1/4*8-4
x=8
y=-2
x=8
------------------------
b)
3x+4y=1⅔
6x+3y=1¼
3x=1⅔-4y
6x+3y=1¼
x=5/9-4/3y
6(5/9-4/3y)+3y=1¼
x=5/9-4/3y
10-8y+3y=1¼
x=5/9-4/3y
-5y=1¼-10
x=5/9-4/3y
-5y=-35/4 /*(-1)
x=5/9-4/3y
5y=35/4
x=5/9-4/3y
y=7/4
x=5/9-4/3*7/4
y=7/4
x=-1 7/9
y=1 3/4
½x-2y=8
2x+5y=6
-2y=8-1/2x /*(-1)
2x+5y=6
2y=1/2x-8
2x+5y=6
y=1/4x-4
2x+5(1/4x-4)=6
y=1/4x-4
2x+5/4x-20=6
y=1/4x-4
13/4x=6+20
y=1/4x-4
13/4x=26
y=1/4x-4
x=26*4/13
y=1/4x-4
x=8
y=1/4*8-4
x=8
y=-2
x=8
------------------------
b)
3x+4y=1⅔
6x+3y=1¼
3x=1⅔-4y
6x+3y=1¼
x=5/9-4/3y
6(5/9-4/3y)+3y=1¼
x=5/9-4/3y
10-8y+3y=1¼
x=5/9-4/3y
-5y=1¼-10
x=5/9-4/3y
-5y=-35/4 /*(-1)
x=5/9-4/3y
5y=35/4
x=5/9-4/3y
y=7/4
x=5/9-4/3*7/4
y=7/4
x=-1 7/9
y=1 3/4
a)½x-2y=8 /*2
2x+5y=6
x-4y=16
2x+5y=6
x=16+4y
2(16+4y)+5y=6
x=16+4y
32+8y+5y=6
x=16+4y
13y=6-32
x=16+4y
13y=26 /:13
x=16+4y
y=2
x=16+4*2
y=2
x=16+8
y=2
x=24
y=2
3x+4y=1⅔
6x+3y=1¼ /:3
3x+4y=1⅔
2x+y=¹₂
3x+4y=1⅔
y=¹₂ -2x
3x+4(¹₂ -2x)=1⅔
y=¹₂ -2x
3x+2-8x=1⅔
y=¹₂ -2x
-5x=1⅔-2
y=¹₂ -2x
-5x=¹₃ /:(-5)
y=¹₂ -2x
x=¹₁₅
y=¹₂ -2x
x=¹₁₅
y=½-2*¹₁₅
x=¹₁₅
y=½ - ²₁₅
x=¹₁₅
y=¹¹₃₀
2x+5y=6
x-4y=16
2x+5y=6
x=16+4y
2(16+4y)+5y=6
x=16+4y
32+8y+5y=6
x=16+4y
13y=6-32
x=16+4y
13y=26 /:13
x=16+4y
y=2
x=16+4*2
y=2
x=16+8
y=2
x=24
y=2
3x+4y=1⅔
6x+3y=1¼ /:3
3x+4y=1⅔
2x+y=¹₂
3x+4y=1⅔
y=¹₂ -2x
3x+4(¹₂ -2x)=1⅔
y=¹₂ -2x
3x+2-8x=1⅔
y=¹₂ -2x
-5x=1⅔-2
y=¹₂ -2x
-5x=¹₃ /:(-5)
y=¹₂ -2x
x=¹₁₅
y=¹₂ -2x
x=¹₁₅
y=½-2*¹₁₅
x=¹₁₅
y=½ - ²₁₅
x=¹₁₅
y=¹¹₃₀